Učinek hipoksije na prekrvljenost kože pri človeku - Golja, Petra (Medicinski razgledi, 2002)
Anecdotal evidence suggests that high altitude increases proneness to cold injury. Since local skin blood flow is the major determinant of the occurrenceof cold injury, any non-thermal factor which enhances vasoconstriction could also increase proneness to cold injury. This research examined whether hypoxia is such a factor. Skin blood flow was monitored indirectly by measuring skin temperature and using infrared thermography. Several environmental temperatures (10 degrees, 24 degrees, 28 degrees and 35 degrees C) and four different altitudes (0, 4000, 5600 in 6300 m) were simulated in the experiment. High altitude was simulated by breathing hypoxic gas mixtures containing known amounts of oxygen. The results of the study indicate that environmental temperature overrides the local vasoconstrictive effects of hypoxia in the skin in cold and warm environment. Hypoxia produces vasoconstriction in the skin in thermoneutral environments, however this effect is small and transient. It was concluded that hypoxia does not locally increase proneness to cold injury, since it does not enhance cold-induced vasoconstriction in cold environment.
Keywords: hipoksija; mraz; prekrvavitev; koža